On the post-unification development of public and private pay in Germany - Axel Heitmüller; Kostas Mavromaras (Institute for the Study of Labor (IZA), 2005)
German post-unification in the 1990s is a period that was marked by substantial economic change, part of which was East German wages building towards the much higher West German levels. This paper studies the public-private pay gap in the fast changing economic and political environment of the 1990s using panel estimation techniques which control for unobserved individual heterogeneity. It shows that, while the overall pay gap between public and private sector stayed remarkably constant in the West, earnings differences in the East increased threefold in the late 1990s resulting in a substantial wage premium in the public sector. It is suggested that this premium is a result of the politically induced gap between pay and actual productivity. Furthermore, results vary greatly by gender indicating significantly larger female earnings differentials. Several institutional and political arguments are presented to explain this phenomenon.
Keywords: J78; J31; 330; public-private sector pay differential; decomposition; Germany; Regionale Lohnstruktur; Privatwirtschaft; Öffentlicher Sektor; Neue Bundesländer; Alte Bundesländer